Political Expression on Social Media: The Role of Communication Competence and Expected Outcomes. (March 2017) - Velasquez, Alcides; Rojas, Hernando
The use of social media sites for political expression has added a new layer to the study of political discussion. In this type of user-generated content applications, interpersonal and mass-mediated types of communication converge in one medium. Therefore, in this study, we bring together insights from interpersonal communication theories and mass communication models that predict online expression, adding explanatory power to this form of political participation. Specifically, we contribute to the understanding of social media political expression by examining the influence of communication competence and expected outcomes on expressive behaviors. Results of a representative survey of the adult urban population of Colombian Facebook ( n = 598) and Twitter ( n = 185) users, suggest that social media communication competence and expected status, novelty, and social outcomes influence political expression on social media. Furthermore, users' social media political expression expected outcomes through Facebook and Twitter differ. This study illustrates the important role that interpersonal communication factors have for social media political discussion, and the difference between users' expectations when they express their political views through different social media platforms.